Investigation of the distribution and antifungal susceptibility of Candida species isolated from clinical specimens in central part of Turkey - Burak Ezer; Selin Ugrakli; Enes Kasapoglu (Journal of Infection in Developing Countries, 2025)
Introduction: This study aimed to examine the distribution and antifungal susceptibility of Candida species in a university hospital and investigate the association of Candida species with age, gender, and clinical specimens.